An assessment of stock market application to speculative transactions for socio-economic growth. (2022) - Kumar Gupta, Sandeep; Reznik, Nadiia P; Cherkasov, Andrii V.; Kozhemiakina, Svitlana M; Levkina, Ruslana V
Abstract: The article considers examples of the use of financial instruments as integral elements of speculative transactions in the stock market. The general trend of world exchange trade is described, considering the influence of various factors on the market situation. Partial analysis of fundamental and technical factors is used. One of the options trading options was used as a clear example of the practical use of derivative financial instruments. The authors point out the main advantages and disadvantages of options trading, emphasizing a rational approach to the choice of trading strategy and market analysis in general. It is emphasized that the choice of strategy and principle of trade is purely individual, where each market participant has its point of view, so decision-making ultimately leads to the responsibility of the trader. Emphasis is placed on the specificity and uniqueness of options trading, which is always accompanied by complexity, risks and is always associated with potential losses.